Relationship between Temperature, Density Residential, Knowledge, Attitude with Density of Larvae in Sub District Gunung Anyar, Surabaya - Ika Prastiani; Corie Indria Prasasti (Universitas Airlangga, 2017)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus and transmitted by mosquito Aedes. Surabaya is one of the districts in East Java Province which includes dengue endemic areas, particularly in Sub district Gunung Anyar. The purpose of this study was analyze relationship between temperature, density residential, knowledge and attitude about the incidence and the intervention of dengue with the density of larvae Aedes aegypti in Sub district Gunung Anyar, Surabaya. This study was an observational study with cross sectional study design that used primary data like observation, interview 100 respondents with cluster random sampling. The dependent variable was density of larvae Aedes aegypti in Sub district Gunung Anyar. The independent variable was temperature, density residential, knowledge and attitude about the incidence and the intervention of dengue. The results showed that variables related with the density of larvae Aedes aegypti in Sub district Gunung Anyar was temperature (p = 0.000), density residential (p = 0.000), knowledge (p = 0.022) and attitude (p = 0.000). There was relationship between temperature, density residential, knowledge and attitude about the incidence and the intervention of dengue with density of larvae in Sub district Gunung Anyar, Surabaya. Health Center and Health Department should do public counseling routinely to increase public knowledge about the incidence and prevention of dengue.